PRECONDITIONS FOR SUCCESS OF VOCATIONAL COUNSELLING OF PUPILS HAVING SPECIAL EDUCATIONAL NEEDS - Baranauskienė, Ingrida; Valaikienė, Aistė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
In contemporary society that is getting more and more modern maximal revelation of person’s possibilities, successful adaptation to the needs of labour market have great importance, therefore, effective and timely vocational counselling has decisive influence on person’s successful socialization and integration. The most vulnerable part of the society – people having special educational needs (SEN) belongs to the great risk group that is at risk to experience social exclusion, become long-term unemployed and find themselves below the limit of poverty. In 2011 in Lithuania the action research was performed in which 95 students having SEN participated. During the research internal and external factors conditioning the success of vocational counselling have become distinct. Stable relations in a family, adequate evaluation of one’s wishes and possibilities, early planning of vocational career are important preconditions for vocational adaptation of students having SEN.